Is vaccination against hepatitis B a reality among Primary Health Care workers? - Fernanda Marques da Costa; Andréa Maria Eleutério de Barros Lima Martins; Pedro Eleutério dos Santos Neto; Duran Nunes de Pinho Veloso; Vilma Soares Magalhães; Raquel Conceição Ferreira (Universidade de São Paulo, 2013)
OBJECTIVE: To verify the prevalence and factors associated with vaccination against hepatitis B among Primary Health Care workers in Montes Claros/MG. METHOD: A cross-sectional, analytic study was undertaken. Data were collected through a form, which contained sociodemographic, occupational, general health and behavioral variables. Associations were investigated through bivariate analysis and Poisson's multivariate regression, using SPSS 17.0. RESULTS: 95.5% answered the question about vaccination; 47.5% did not complete the vaccination scheme. The prevalence of vaccinated professionals was lower among older workers, who were hired, did not participate in occupational health updates and consumed alcohol. Prevalence levels were higher among professionals with more years of education and who reported contact with piercing and cutting instruments . CONCLUSIONS: Professional education, knowledge and perception of infection risks are important determinants of the vaccination scheme. Instability at work may lead to negligence and negligent behaviors may repeat themselves. The characterization of professionals who did not get vaccinated will direct educative actions in occupational health.